Ligand switch in photoinduced copper-mediated polymerization: synthesis of methacrylate–acrylate block copolymers. Issue 36 (6th August 2015) - Chuang, Ya-Mi; Wenn, Benjamin; Gielen, Sam; Ethirajan, Anitha; Junkers, Thomas
Abstract : The use of photo-induced copper-mediated radical polymerization (photoCMP) to synthesize mixed acrylate/methacrylate (methyl acrylate, MA and methyl methacrylate, MMA) block copolymers is investigated. Abstract : The use of photo-induced copper-mediated radical polymerization (photoCMP) to synthesize mixed acrylate/methacrylate (methyl acrylate, MA and methyl methacrylate, MMA) block copolymers is investigated. Reactions in which only one type of ligand (Me6 TREN) is used lead to unsuccessful outcomes of polymerization due to a mismatch in reactivity of the two monomers. A ligand exchange to PMDETA for methacrylate is required to obtain good block structures. Due to insufficient re-initiation of polyacrylates, methyl methacrylate needs to be polymerized first, before acrylate can be added for chain extension. A halogen exchange with CuCl is found to be beneficial to increase the re-initiation behaviour of the polyacrylate with respect to the acrylate chain propagation, but inherently compromises the livingness of the polymerization. Successful synthesis of block copolymers is only observed when the PMMA block is polymerized first and if all PMDETA ligand and residual monomer are removed prior to acrylate chain extension. The batch-type photoreactions are then transferred to a continuous flow tubular photoreactor, which leads to a significant acceleration of polymerizations, concomitant reduction in product dispersity and largely simplified block copolymer synthesis conditions.